1999
DOI: 10.1055/s-2008-1053362
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic Third Ventriculostomy in the Management of Fourth Ventricular Outlet Obstruction

Abstract: Acquired fourth ventricular outlet obstruction, an uncommon entity, has been conventionally managed by ventriculoperitoneal shunt placements or excision of the obstructing membranes. The role of endoscopic third ventriculostomy is highlighted in the present communication. Three patients presenting with symptoms of raised intracranial pressure were diagnosed to have fourth ventricular outlet obstruction by neuroimaging studies and underwent endoscopic third ventriculostomy. All the patients had relief of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…Although FVOO has recently been treated successfully by NTV [20,22], this could not be attempted in this case, because the floor of the third ventricle was tightly adherent to the dorsum sellae. This adhesion provided further support for the assumption of long-standing hydrocephalus.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although FVOO has recently been treated successfully by NTV [20,22], this could not be attempted in this case, because the floor of the third ventricle was tightly adherent to the dorsum sellae. This adhesion provided further support for the assumption of long-standing hydrocephalus.…”
Section: Discussionmentioning
confidence: 64%
“…However, the radiographic findings of digital impressions and osteolytic changes in the dorsum sellae indicated long-standing, presumably congenital, hydrocephalus. FVOO, a rare but recognized cause of hydrocephalus [1,15,20,21,22,23], was diagnosed in our patient by CT cisternography.…”
Section: Discussionmentioning
confidence: 86%
“…Another alternative procedure, third ventriculostomy, is a reasonable treatment option to create a diversion for CSF. Mohanty et al [6]reported three cases of acquired fourth ventricle outlet obstruction who received third ventriculostomy with decreased ventricular size postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Although ETV has emerged as the preferred treatment for obstructive hydrocephalus from etiologies such as aqueductal stenosis [2, 4, 5, 7, 8, 9, 10, 11, 12], tectal plate gliomas [3, 6, 13]and fourth ventricular outflow obstruction [20], relatively few studies have addressed its utility in patients with posthemorrhagic and postinfectious hydrocephalus. This likely reflects the traditional concept that these processes cause hydrocephalus from distal obstruction of CSF reabsorption at the level of the arachnoid granulations.…”
Section: Discussionmentioning
confidence: 99%